Mr. Nice - Marks, Howard (Secker & Warburg, 1996)
This is the true story of Howard Marks. He was Britain's most wanted man. He spent seven years in America's toughest penitentiary. You'll like him. During the mid 1980s Howard Marks had forty three aliases, eighty nine phone lines and owned twenty five companies throughout the world. Whether bars, recording studios or offshore banks, all were money laundering vehicles for his main concern: dope dealing. At the height of his career he was smuggling up to thirty tons of marijuana and had contact with organisations as diverse as MI6, the CIA, the IRA and the Mafia. Following a worldwide operation by the Drugs Enforcement Agency, he was busted and sentenced to twenty-five years at a state penitentiary in Indiana. He was released in 1995 after serving seven years of his sentence. This is his story. What an extraordinary fellow Howard Marks is. His autobiography takes him from his South Wales childhood and Oxford University education through his life dealing marijuana and the enormous mythology that accrued around what the tabloids called "the English Toff Drugs King of the World". This book is called Mr Nice after one of the many aliases Marks's life as a merchant of pot obliged him to assume, but it describes him perfectly too: the epitome of British niceness, the nicest international criminal you could hope to meet. It's not hard to see why this has become a cult book--Marks is a brilliant version of a mate down the pub, telling you the gobsmacking stories of his many adventured life. The writing is direct and the narrative will detain you as comprehensively as Marks himself was detained for seven years at Terre Haut Penitentiary, Indiana. He was released the same day as Mike Tyson. "I had," he observes mildly, "been continuously in prison for the last six-and-a-half years for transporting beneficial herbs from one place to another, while he had done three years for rape." Truly there is no justice; but there are eye-popping adventures, hilarious touches and a thorough-going wisdom in this excellent book.